Le dioula véhiculaire : Situation sociolinguistique en Côte d’Ivoire - Konate Yaya (Corela)
Our present article intends to present the role of vehicular dioula in Côte d’Ivoire. Indeed, many studies have already been made on the language in question, showing how the language is dynamic and important as well as economically and socially. The present article aims to show that special place that has this language through different surveys Ivorian people.